Design and Analysis of Industrial Safety Helmet - Mishra, Sandhya; Khoteja, Rejsha; Mahat, Chiranjeevi (Kathmandu University Journal of Science, Engineering and Technology, 2021)
The safety of the workers is a valuable asset in every organization. A safety helmet is one of the personal protective equipment to ensure the user’s head against the impact of heavy loads in work sites. This study presents the optimized design of the shell of locally used safety helmets in Nepal’s industries and works sites. The study is based on the cohesive findings from qualitative and quantitative research. The interviews were carried out in Mahindra Auto Works Pvt. Ltd. and Dhulikhel Hospital. Questionnaire data were collected from Udayapur Cement Industries Ltd., Balaju Industrial Area and Patan Industrial Area, which helped identify the problems in Nepal’s existing safety helmets. The issues identified were headache due to extra weight, insufficient ventilation, adjustment and fitting problem, insufficient peak, inadequate aesthetic look, tight chin strap. The data from Dhulikhel Hospital interpreted anatomy of head and was considered to proceed with the new design of helmet shell. The 3D design of the shell of the newly designed helmet and the existing helmet was done in SolidWorks, and their simulation was carried out in ANSYS Workbench 15. The comparison of old and new models was done for static, dynamic and compression test considering the varying cases and force magnitudes. This study concludes that the total deformation and equivalent stress of the new model were less than that of the old model.